Organization of Planning in Preschool Educational Institutions (Eurasian Journal of Humanities and Social Sciences, 2023)
Educational process in preschool educational institutions largely depends on the quality of its planning. Planning includes setting goals, developing rules and sequences of actions, anticipating and forecasting results.